Appraisal of comparative single-case experimental designs for instructional interventions with non-reversible target behaviors: Introducing the CSCEDARS (“Cedars”) - Schlosser, Ralf W.; Belfiore, Phillip J.; Sigafoos, Jeff; Briesch, Amy M.; Wendt, Oliver (Research in developmental disabilities, 2018)
Evidence-based practice as a process requires the appraisal of research as a critical step. In the field of developmental disabilities, single-case experimental designs (SCEDs) figure prominently as a means for evaluating the effectiveness of non-reversible instructional interventions. Comparative SCEDs contrast two or more instructional interventions to document their relative effectiveness and efficiency. As such, these designs have great potential to inform evidence-based decision-making. To harness this potential, however, interventionists and authors of systematic reviews need tools to appraise the evidence generated by these designs. Our literature review revealed that existing tools do not adequately address the specific methodological considerations of comparative SCEDs that aim to compare instructional interventions of non-reversible target behaviors. The purpose of this paper is to introduce the Comparative Single-Case Experimental Design Rating System (CSCEDARS, “cedars”) as a tool for appraising the internal validity of comparative SCEDs of two or more non-reversible instructional interventions. Pertinent literature will be reviewed to establish the need for this tool and to underpin the rationales for individual rating items. Initial reliability information will be provided as well. Finally, directions for instrument validation will be proposed.